2000
DOI: 10.1046/j.1442-2042.2000.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant phyllodes tumor of the prostate

Abstract: We report a case of malignant phyllodes tumor of the prostate which is the eleventh reported case in the world. Phyllodes tumor of the prostate is extremely rare and histologically resembles mammary phyllodes tumor. Phyllodes tumor of the prostate is classified into benign, borderline and malignant, but health professionals should carefully follow up the borderline cases in case they take a malignant clinical course. This case was the first to be treated by pre-and postoperative radiation therapy. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
0
20
2
Order By: Relevance
“…The recurrent sarcoma in the case reported by Young et al 15 was positive for vimentin and desmin, but negative for the other muscle markers: SMA and muscle common antigen. Other cases 19,28,29 showed a similar immunohistochemical profile to that reported by Young et al 15 In contrast, the case reported by Yum et al 7 showed positive reactions to vimentin, and the muscle markers muscle-specific actin, and desmin. Yum et al called it leiomyosarcoma arising in phyllodes tumor.…”
Section: B Prostatic Stromal Sarcoma and Malignant Phyllodes Tumor Ocontrasting
confidence: 68%
See 2 more Smart Citations
“…The recurrent sarcoma in the case reported by Young et al 15 was positive for vimentin and desmin, but negative for the other muscle markers: SMA and muscle common antigen. Other cases 19,28,29 showed a similar immunohistochemical profile to that reported by Young et al 15 In contrast, the case reported by Yum et al 7 showed positive reactions to vimentin, and the muscle markers muscle-specific actin, and desmin. Yum et al called it leiomyosarcoma arising in phyllodes tumor.…”
Section: B Prostatic Stromal Sarcoma and Malignant Phyllodes Tumor Ocontrasting
confidence: 68%
“…Yum et al called it leiomyosarcoma arising in phyllodes tumor. From these cases 15,19,28,29,30,[38][39][40] it appears that PSS can affect patients with a wide age range, and the prognosis is dependent on the grade and stage of disease.…”
Section: B Prostatic Stromal Sarcoma and Malignant Phyllodes Tumor Omentioning
confidence: 95%
See 1 more Smart Citation
“…Lam and Yeo9 reported the efficacy of chemotherapy with ifosfamide and doxorubicin for lung metastasis after radical prostatectomy, in addition to adjuvant irradiation. Yamamoto10 reported that radiation therapy is limited to patients with metastatic tumors, and Mizuaki11 reported the effects of VIP chemotherapy as induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…17,[51][52][53][54][55][56][57][58][59][60][61] There are at least two reported cases of stromal sarcoma of the 'phyllodes type' arising in the seminal vesicle without involvement of the prostate. 62 suggesting a potential for STUMPs to dedifferentiate into sarcomas in rare cases and justifying the term 'malignant potential' for STUMPs.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%